Isolation and Characterization of Suppressors of Two Escherichia Coli Dnag Mutations, Dnag2903 and Parb - Britton, R. A. (1997)
The dnaG gene of Escherichia coli encodes the primase protein, which synthesizes a short pRNA that is essential for the initiation of both leading and lagging strand DNA synthesis. Two temperature-sensitive mutations in the 3' end of the dnaG gene, dnaG2903 and parB, cause a defect in chromosome partitioning at the nonpermissive temperature 42°. We have characterized 24 cold-sensitive suppressor mutations of these two dnaG alleles. By genetic mapping and complementation, five different classes of suppressors have been assigned: sdgC, sdgD, sdgE, sdgG and sdgH. The genes responsible for suppression in four of the five classes have been determined. Four of the sdgC suppressor alleles are complemented by the dnaE gene, which encodes the enzymatic subunit of DNA polymerase III. The sdgE class are mutations in era, an essential GTPase of unknown function. The sdgG suppressor is likely a mutation in one of three genes: ubiC, ubiA or yjbI. The sdgH class affects rpsF, which encodes the ribosomal protein S6. Possible mechanisms of suppression by these different classes are discussed.